The Concept of Surface Layer in Technical Aesthetics and its Properties - Nurmakhanov , Баймахан; Марк, Ислам (Рroblems of engineering and professional education, 2025)
The article discusses the concept of the surface layer in technical aesthetics and its role in the structure of finishing and facing materials. Functional, aesthetic and symbolic properties of the surface are determined on the basis of its categories. The surface layers of materials determine their structural characteristics and visual impact, which plays an important role in design and architecture. The article discusses the geometric classification of surfaces, their relationship with shape and the meaning of surface texture. A close relationship is established between the functional and aesthetic properties of the surface, which take into account not only the technical characteristics of the material, but also the psycho physiological perception of a person. The article discusses the technology of using finishing and facing materials in various industries, which is associated with the technical design of materials, which have recently reached a new qualitative level. The introduction and development of surface design technologies in the construction industry opens up wide opportunities for the implementation of individual design projects. In recent years, a new market has emerged in the production of finishing and facing materials, new developments in surface finishing systems have emerged, differing in texture, texture and color. This study provides a deeper understanding of the conceptual meaning of the surface layer in technical aesthetics.